2014
DOI: 10.1016/j.ijscr.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Large adrenal ganglioneuroma

Abstract: This case suggests that ganglioneuromas can wrongly be diagnosed as other adrenal tumors. It is significant that a proper differential diagnosis should be performed by using hormonal and imaging techniques. Nevertheless, pathological examination is usually required for definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…12 In addition, tumour size is a crucial decisive factor for the prognosis of adrenal tumorus. 7 Hence, this current study analysed the AGNs based on their tumour size using a cut-off medium diameter of 3 cm. The current results demonstrated that there was no difference in location between large and small AGNs, which was consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, tumour size is a crucial decisive factor for the prognosis of adrenal tumorus. 7 Hence, this current study analysed the AGNs based on their tumour size using a cut-off medium diameter of 3 cm. The current results demonstrated that there was no difference in location between large and small AGNs, which was consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Only sporadic case reports or small patient populations have been reported. [7][8][9][10] Reports on the CT features of AGNs show wide variations and it can be difficult to differentiate AGNs from other adrenal neoplasms including adrenal adenoma, adrenocortical carcinoma and pheochromocytoma. 9,11 Hence, it is a challenge for radiologists to achieve a precise diagnosis of AGNs ahead of any planned surgery.…”
Section: Introductionmentioning
confidence: 99%
“…La cirugía se realizó sin eventualidades, y el paciente nales es de 0.2% en pacientes jóvenes, 3% en la población mayor de 50 años y hasta de 7% después de los 70 años, de los cuales los Ganglioneuromas adrenales representan entre el 0-6% de los casos. (2,8) Anteriormente se consideraba que la mayor prevalencia era en niños y adultos jóvenes entre 10-40 años, (4,9) sin embargo, estudios más recientes, reportan que en EUA, China, Canadá y Grecia, la edad media de diagnóstico es de 31, 39.2, 49 y 50 años respectivamente. (10) La distribución por sexos es similar en hombres y mujeres.…”
Section: Presentación Del Casounclassified
“…(2,5) Debe diferenciarse del feocromocitoma mediante el estudio de catecolaminas y/o metanefrinas en orina y séricas, sin embargo, a pesar de la sensibilidad y especificidad de estos estudios, el diagnóstico definitivo es histopatológico. (8) En la tomografía computada, se muestra como una masa redonda u ovalada, homogénea y bien circunscrita, ligeramente hipodensa, en ocasiones con calcificaciones puntiformes, que presenta atenuación en la fase simple <40 uh y no muestra realce o presenta un reforzamiento muy leve en la fase contrastada. (3,5) Sin embargo, basándose únicamente en estudios de imagen es prácticamente imposible diferenciar este tipo de lesiones de un adenoma adrenal, carcinoma adrenocortical o feocromocitoma.…”
Section: Presentación Del Casounclassified
See 1 more Smart Citation